Why did the perfect marriage end : case Cloetta Fazer - Pitkänen, Aki (My University, 2013)
Mergers are often used purposeful strategic tool. Previous research has mainly concentrated on actu-al M&A process and to elements leading to that decision. Purpose of this study is to approach de-merger of Cloetta Fazer and research what were the reasons that lead to demerger. Problem is ap-proached by first evaluating was the merger an success in the first place, as described in earlier stud-ies, media and academic research. From this information the motives for demerger are approached. Research material for study is collected from second hand sources. Research data-sample was di-vided into two categories: Timeline Sample & Additional Information Sample. Timeline sample was collected by systematically collecting news from Sanoma News database and Alma News database. This data was indexed and a timeline was constructed. From this timeline key dates, themes and elements were identified and further data gathering was concentrated based on those themes. Results of the study suggest that Merger was not as great success as it was described in earlier years. Explanations why merger ended up into demerger vary greatly. From material key factor, lack of, or error in, long term strategic planning was identified. This was due to death in family during strategy creation and mistakes made in pre-merger phase.